The Energetic Nitrocarbamate O2NN(H)CO[OCH2C(NO2)3] Derived from Phosgene. Issue 1 (17th October 2013) - Axthammer, Quirin J.; Klapötke, Thomas M.; Krumm, Burkhard; Moll, Richard; Rest, Sebastian F.
Abstract A new simple synthesis route for 2, 2, 2‐trinitroethyl chloroformate (1), from easily available starting materials 2, 2, 2‐trinitroethanol and phosgene is presented. 2, 2, 2‐Trinitroethyl carbamate (2) was obtained by the reaction of 1 with aqueous ammonia. The nitration of 2 with anhydrous nitric acid and sulfuric acid yields 2, 2, 2‐trinitroethyl nitrocarbamate (3), which has potential as a perchlorate free high energetic dense oxidizer with a high oxygen balance of Ω(CO2) = +14.9 %. The thermal stability was studied using differential scanning calorimetry and the energies of formation were calculated on the CBS‐4M level of theory, as well as several detonation parameters and propulsion properties were determined. In addition to full spectroscopic characterization, X‐ray diffraction studies were performed for 2 and 3.